"Just Look at her!": Sporting Bodies as Athletic Resistance and the Limits of Sport Norms in the Case of Caster Semenya. (August 2015) - Miller, Shane Aaron
Using the American sport media's treatment of South African runner Caster Semenya, this article explores how in the course of defending Caster Semenya the American sport media presented a rigorous challenge to traditional conceptions of sex and gender. Yet these rhetorical efforts to deconstruct sex and gender binaries were undermined by the specific ways in which Semenya's dual performances—athletic and gender—were visually depicted. A close reading and analysis of US sports media coverage of Caster Semenya provide an opportunity to explore the ways in which the norms of sport may foster progressive treatment of athletes whose genders do not fit comfortably within the existing, traditional expectations of what men and women should be like. At the same time, however, I wish to suggest that both discursive and visual rhetoric are limited in how much they can use such sports norms when ontological questions about the normal, the natural, and the body are at stake. By paying particular attention to the interplay between the linguistic, the visual, and the performative, I hope to show that even the most sincere efforts to complicate sex and gender within the framework of sport have significant limitations.